ANALISIS KESALAHAN SISWA PADA HASIL UJIAN TENGAH SEMESTER MATEMATIKA DI KELAS VIII SMP BALA KESELAMATAN BALAMOA PADA SEMESTER GENAP BERDASARKAN METODE NEWMAN: Analysis of Error in Mathematics Middle Semester Examination Results at Grade VIII Students of SMP Bala Keselamatan Balamoa in Even Semester Based on Newman Method - K, Olpi Jenli; Awuy, Evie; Sukayasa (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
This research is aimed to obtain error description by students on math midterm at SMP Bala Keselamatan Balamoa based on Newman. This research is descriptive research which used qualitative approach. The data was collected using documentation and interview. The result shows that: (1) the kind of numerical pattern material is a mistake in comprehension error (comprehension error), transformation error (transformation error), process skill error (process skill error), and encoding error (encoding error). (2) kind of errors in kartesius coordinate is comprehension error (comprehension error), transformation error (transformation error), and encoding error (encoding error). (3) error in relation and function material is comprehension error (comprehension error), transformation error (transformation error), and encoding error (encoding error).